An intranasally administered monoclonal antibody cocktail abrogates ricin toxin-induced pulmonary tissue damage and inflammation - Yinghui Rong; Fernando J. Torres-Velez; Dylan Ehrbar; Jennifer Doering; Renjie Song; Nicholas J. Mantis (Taylor & Francis Group, 2020)
Ricin toxin, a plant-derived, mannosylated glycoprotein, elicits an incapacitating and potentially lethal inflammatory response in the airways following inhalation. Uptake of ricin by alveolar macrophages (AM) and other pulmonary cell types occurs via two parallel pathways: one mediated by ricin's B subunit (RTB), a galactose-specific lectin, and one mediated by the mannose receptor (MR;CD206). Ricin's A subunit (RTA) is a ribosome-inactivating protein that triggers apoptosis in mammalian cells. It was recently reported that a single monoclonal antibody (MAb), PB10, directed against an immunodominant epitope on RTA and administered intravenously, was able to rescue Rhesus macaques from lethal aerosol dose of ricin. In this study, we now demonstrate in mice that the effectiveness PB10 is significantly improved when combined with a second MAb, SylH3, against RTB. Mice treated with PB10 alone survived lethal-dose intranasal ricin challenge, but experienced significant weight loss, moderate pulmonary inflammation (e.g., elevated IL-1 and IL-6 levels, PMN influx), and apoptosis of lung macrophages. In contrast, mice treated with the PB10/SylH3 cocktail were essentially impervious to pulmonary ricin toxin exposure, as evidenced by no weight loss, no change in local IL-1 and IL-6 levels, retention of lung macrophages, and a significant dampening of PMN recruitment into the bronchoalveolar lavage (BAL) fluids. The PB10/SylH3 cocktail only marginally reduced ricin binding to target cells in the BAL, suggesting that the antibody mixture neutralizes ricin by interfering with one or more steps in the RTB- and MR-dependent uptake pathways.